Paleo-landscapes of the Northern Patagonian Massif, Argentina - Aguilera, Emilia Yolanda (2014)
The dominant geomorphological unit of the Northern Patagonian Massif landscape is a regional planation surface, eroded across the crystalline basement (plutonic and metamorphic rocks), eruptive rocks of the Gondwana cycle (Early to Middle Carboniferous), and Jurassic volcanic rocks. The most important active climate during the genesis of this surface had a very significant role, developing intense chemical weathering extending to variable depths with the corresponding degradation of the rocky material exposed at the surface. Remnants of the weathering profiles, both outcropping and fossilized by burial, are identified and described. Such a particular mega-landform was developed in a cratonic environment, mainly as a product of deep weathering, and it is interpreted as a denuded surface, an etchplain formed by corrosion followed by erosion. The analysis of the relationships between relief, saprolite, and rock cover throughout time suggests that the most important factor for the classification of the present landscape is the duration of exposure of the crystalline basement at the surface, from the end of the Paleozoic and during the entire Mesozoic. This conclusion has essential relevance for the evaluation of the effects of Mesozoic tectonics and the powerful weathering under certain climatic conditions. It is estimated that this paleosurface would have initiated its development towards the end of the Paleozoic, but later modifying also the Jurassic volcanic rocks that preceded the rifting processes that lead to the opening of the Southern Atlantic Ocean. Finally, the tectonic activity during the early Tertiary produced the exhumation of the planation surface, which was buried by its own regolith, reactivating erosion surfaces and small drainage basins. However, it is possible that some areas of the planation surface had never been covered by other rocks, other than its own overlying weathering products. Our results suggest that the landscape features should not be assigned to Quaternary morphogenesis, but instead, they have evolved over a very long time, perhaps 100 Ma or even more. These observations refer to Mesozoic times, and therefore the time scale used for the discussion of the geomorphology of the Northern Patagonian Massif should be enlarged to properly analyze the evolution of the ancient landscapes of this cratonic region. This chapter contributes to the analysis of comparative studies of global geomorphology of cratonic areas, where planation surfaces record very long periods in which the speed of crustal deformation is highly compensated by planation processes.